Operative treatment of tertiary hyperparathyroidism: a single-center experience. - Kerby, J D (1998)
OBJECTIVE: To review the experience with the operative treatment of tertiary hyperparathyroidism (TH) from a single renal transplant center. SUMMARY BACKGROUND DATA: Most patients with chronic renal failure show evidence of secondary hyperparathyroidism by the time maintenance hemodialysis begins. Persistent secondary hyperparathyroidism (i.e., TH) requiring surgical intervention is uncommon in the authors' experience. METHODS: Charts of patients who underwent parathyroidectomy for TH were reviewed retrospectively. Information obtained included demographics, laboratory data, symptoms, operative procedure (including morbidity and mortality rates), and pathology. Comparisons of demographic data and allograft survival were made between the transplant population as a whole and a matched cohort group of patients. RESULTS: Thirty-eight patients from 4344 renal transplant procedures during a 29-year period required parathyroidectomy for TH. All patients had hypercalcemia; 20 were asymptomatic and 18 had varying symptoms. Mean time from renal transplantation to parathyroidectomy was 997 +/- 184 days, with a mean preoperative calcium level of 12.2 +/- 0.14 mg/dl. Total parathyroidectomy with parathyroid autograft was performed in 26 of 34 primary procedures. There were no deaths. The operative morbidity rate was 6% (wound separation and vocal cord hemiparesis, one each). Pathology was reported in all patients and recently reviewed in 28 patients. Twenty-four had diffuse hyperplasia and nine had nodular hyperplasia; one had an adenoma. Parathyroid glands diagnosed as nodular hyperplasia were significantly larger by total mass than those with diffuse hyperplasia. Comparison of allograft survival between the study group and a matched cohort group of patients revealed no difference in long-term graft survival. CONCLUSIONS: Operative intervention is recommended in patients with an asymptomatic increase in serum calcium to >12.0 mg/dl persisting for >1 year after the transplant, acute hypercalcemia (calcium >12.5 mg/dl) in the immediate posttransplant period, and symptomatic hypercalcemia.